Contribution to the study of some aspects of pollination in six varieties of apricot in the region of M'sila (Algeria) - R. Benmehia, H. Bendif; A. Zedam, F. Bahlouli, S. Tellache, A. Slamani (Journal of Scientific Agriculture, 2017)
The present work consists in contributing to the study of pollination. Field observations and tests were carried out on six varieties of apricot in the region of M'sila, "Pavit", "Boulida" "Alarbi","Tounsi","Ben sarmouk" and "Louzi rouge". For natural self-pollination, the branches were covered to avoid cross-pollination, and the fruit set was determined. Controlled pollination was carried out using pollen and pollen from the other trees that bloom at about the same time. The fruit set rate was determined after counting the fruits in relation to the number of blooming flowers. The rate of fruit set varies from one variety to another. Alarbi with 62.5%, Louzi with 69.7%, Tounssi with 56.5%, Bulida with 50.7%, Ben Sermouk with 23.2% and Pavit with 45.8%. The bagging rate of the bagged branch obtained at the end of the physiological fall did not show any significant differences between the varieties and ranged between 77.50% for Alarbi and 41.22% for Pavit. The results show that the number of fruits after manual crossing is zero for all crops. All varieties tested are self-compatible and no cross-compatibility group has been guessed on the tested growths, from self-pollination and inter-pollination.